SINERGI KESELAMATAN KERJA DAN DISIPLIN KERJA TRANSFORMASI KINERJA KARYAWAN PADA PT. SUPRA PRIMATAMANUSANTARACABANG KEDOYASELATAN JAKARTA BARAT - Human Fikri Nur Aziz; Ading Sunarto (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study aims to analyze the synergy effect between occupational safety and work discipline on the transformation of employee performance at PT. Supra Primatama Nusantara, Kedoya Selatan Branch, West Jakarta. The background of the study is based on the phenomena of underachievement of work targets, high rates of lateness and absenteeism, and low compliance with workplace safety regulations. This research uses a quantitative approach with data collected through questionnaires distributed to 65 respondents. The results show that both occupational safety and work discipline, partially and simultaneously, have a significant effect on employee performance. The research results show that: (1) Partially, occupational safety has a positive effect on employee performance. This can be proven through the linear regression test which yields the regression equation Y = 4.355 + 1.887 X₁. It can be concluded that the constant value is 4.355. The t-test produces a t-calculated value of 4.355, and the t-table value at the 5% significance level is 1.66940. Since t- calculated (4.355) > t-table (1.66940) with a significance level of < 0.05, namely 0.004, the result is significant. (2) Partially, work discipline also has a positive effect on employee performance. This is demonstrated through the linear regression equation Y = 4.355 + 2.774 X₂, showing a constant value of 4.355. The t-test results in a t-calculated value of 4.355, which is greater than the t-table value of 1.66940. The significance value is 0.007, which is less than 0.05, indicating a significant effect. (3) Simultaneously, occupational safety and work discipline have a positive effect on employee performance. This is proven by the multiple linear regression equation Y = 4.355 + 1.887 X₁ + 2.774 X₂, which shows a constant of 4.355. This means that if the occupational safety variable (X₁) increases by one unit, employee performance (Y) will increase by 1.887 units, and if the work discipline variable (X₂) increases by one unit, employee performance (Y) will increase by 2.774 units. The simultaneous hypothesis test using the F-test shows that F-calculated > F-table (46.933 > 3.145) with a significance value of 0.001 < 0.05, indicating a statistically significant simultaneous effect.